On ideal convergence of rough triple sequence - Ömer Kişi; Mehmet Gürdal; Ekrem Savaş (E-Journal of Analysis and Applied Mathematics)
In this paper, we present the ideal convergence of triple sequences for rough variables. Furthermore, sequence convergence plays an extremely important role in the fundamental theory of mathematics. This paper presents two types of ideal convergence of rough triple sequence: Convergence in trust and convergence in mean. Some mathematical properties of those new convergence concepts are also given. In addition, we introduce ideal Cauchy triple sequence in rough spaces